Humanistic Education Perspective of the Qur’an and Hadith - Ulum, Anharul; Ride, Ahmad Rozi; Salas, M. Kamil; Asy'arie, Bima Fandi; Al Fajar, Adam Hafidz (Institut Agama Islam Negeri (IAIN) Curup, 2024)
One model of education in Indonesia is humanistic which focuses on communication and is more humane. If implemented correctly, this will certainly help shape students’ identities for the better. The purpose of this study is in order First, to find out the humanistic education perspective of the Qur’an and Hadith. Second, to know the characteristics in terms of humanistic educational patterns of general theory then the perspective of the Quran and Hadith. The method that the author uses in this study is a qualitative method or commonly called literature study. The characteristics of humanistic education include (1) Providing learning materials systematically, which contains Qs. Al-Maidah: 67 and HR. al-Bukhari, Muslim, al-Turmuzi and Imam Ahmad. (2) Provide an attitude of affection and gentleness, which is contained Qs. Ali Imran: 159 and HR. al-Bukhari. (3) Provide students with freedom to learn while in class, which has Qs. Al-Baqarah: 31 and HR. Al-Bukhari. (4) Provide motivation during the learning process, which is Qs. Al-Mujadilah: 11 and HR. Muslim. (5) Give a fair attitude, which is found Qs. Al-Maidah: 8 and HR. An-Nasa’ and Al-Baihaqi. (6) Give awards for the achievements that have been obtained, which are Qs. Al-Qasas: 84 and H.R. Bukhari.